Nanotechnology Based Antimicrobial Agents: A New Strategy Against Antibiotic Resistance - {"name":"Saravanan Ravindran"; "email":"rssrmcp@gmail.com"; "affiliation":"Profes; {"name":"Suresh.K"; "affiliation" of Pharmacy; Bharath Institute of Higher Education and Resea; {"name":"Sarukesh.K"; "affiliatio of Pharmacy; {"name":"Vanitha Sri.T"; "affiliation":"Faculty of; {"name":"Abinaya.S"; "affiliation of Pharmacy (Future Journal of Pharmaceuticals and Health Sciences, 2026)
The successful treatment of infectious diseases is seriously threatened by antibiotic resistance, which has become a major worldwide health concern. The effectiveness of traditional antibiotics has decreased due to the rise in multidrug - resistant bacteria, which has made the creation of new treatment approaches necessary. Because of nanoparticles' unique physicochemical properties, such as a high surface - to - volume ratio, higher reactivity, and improved contact with microbial membranes, nanotechnology has em erged as a promising strategy for combating microbial resistance.Numerous nanomaterials, such as metallic, metal oxide, polymeric, lipid - based, and carbon - based nanomaterials, exhibit potent antibacterial activity against a range of pathogenic microorganisms.These nanoparticles produce reactive oxygen species, interfere with DNA replication, break bacterial cell membranes, and impede enzyme function, among other ways they have antimicrobial effects. Furthermore, the ecologically conscious and sustainable aspect of green nanoparticle synthesis with plant extracts has attracted interest. This study discusses nanoparticle kinds, methods of action, biological uses, toxicity considerations, and future research prospects in order to highlight the promise of nanotechnology - based antimicrobial agents as a novel approach to fight antibiotic resistance.